2013
DOI: 10.1080/10286020.2012.757595
|View full text |Cite
|
Sign up to set email alerts
|

Two new stemona alkaloids fromStemona tuberosaLour.

Abstract: Two new pyrrolo[1,2-α]azepine-type stemona alkaloids, named as tuberostemonoxirine (1) and 9α-epi-tuberospironine (2), were isolated from the roots of Stemona tuberosa. The structures and relative configurations of new compounds were established on the basis of extensive spectroscopic evidences, especially 1D and 2D NMR and HR-MS experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The structures of the isolates were established by analysis of the extensive spectroscopic data (such as HR-ESI-MS, 1D/2D NMR, ORD, and ECD). Among them, compound 1 represents a previously undescribed furfural derivative, and the other twentyfive known compounds (2-26) were identified as 1,4-difuranyl-2,3dihydroxy-1,4-butanedione (2), [8] tuberostemonoxonine (3), [9] didehydrotuberostemonine A (4), [10] N-(4-hydroxyphenethyl)acetamide (5), [11] aurantiamide (6), [12] aurantiamide acetate (7), [13] stilbostemin B 3'-O-β-D-glucopyranoside (8), [14] trans-resveratrol 3-O-β-D-glucopyranoside (9), [15] daidzin (10), [16] rutin (11), [17] emodin-8-O-β-Dglucopyranoside (12), [18] psoralen (13), [19] isopsoralen ( 14), [20] isoacteoside (15), [21] 3,5-dihydroxy-1-(3,4-dihydroxyphenyl)-7-(4hydroxyphenyl)heptane ( 16), [22] (+)-syringaresinol (17), [23] (+)-syringaresinol-4-O-β-D-glucoside (18), [24] hydroxybenzaldehyde (19), [25] 3-hydroxy-4-methoxybenzoic acid (20), [26] 4-methoxybenzoic acid (21), [27] 4-hydroxybenzonic acid ( 22), [28] 1,2,4-benzenetriol (23), [29] caffeic acid (24), [17] 4-hydroxycinnamic acid (25), [30] and protocatechuic acid (26), [31] Analysis of the 1D NMR, HMQC, and HMBC data allowed the overall assignments of the NMR data of 1 as listed in Table 1. Further, NOESY correlations between H 3 -11 and H-2/H-5/H-7, and between H-5 and H-7, indicated that H-2, H 3 -11, H-5, and H-7 were at a relatively close distance in space, or oriented in the same direction.…”
Section: Resultsmentioning
confidence: 99%
“…The structures of the isolates were established by analysis of the extensive spectroscopic data (such as HR-ESI-MS, 1D/2D NMR, ORD, and ECD). Among them, compound 1 represents a previously undescribed furfural derivative, and the other twentyfive known compounds (2-26) were identified as 1,4-difuranyl-2,3dihydroxy-1,4-butanedione (2), [8] tuberostemonoxonine (3), [9] didehydrotuberostemonine A (4), [10] N-(4-hydroxyphenethyl)acetamide (5), [11] aurantiamide (6), [12] aurantiamide acetate (7), [13] stilbostemin B 3'-O-β-D-glucopyranoside (8), [14] trans-resveratrol 3-O-β-D-glucopyranoside (9), [15] daidzin (10), [16] rutin (11), [17] emodin-8-O-β-Dglucopyranoside (12), [18] psoralen (13), [19] isopsoralen ( 14), [20] isoacteoside (15), [21] 3,5-dihydroxy-1-(3,4-dihydroxyphenyl)-7-(4hydroxyphenyl)heptane ( 16), [22] (+)-syringaresinol (17), [23] (+)-syringaresinol-4-O-β-D-glucoside (18), [24] hydroxybenzaldehyde (19), [25] 3-hydroxy-4-methoxybenzoic acid (20), [26] 4-methoxybenzoic acid (21), [27] 4-hydroxybenzonic acid ( 22), [28] 1,2,4-benzenetriol (23), [29] caffeic acid (24), [17] 4-hydroxycinnamic acid (25), [30] and protocatechuic acid (26), [31] Analysis of the 1D NMR, HMQC, and HMBC data allowed the overall assignments of the NMR data of 1 as listed in Table 1. Further, NOESY correlations between H 3 -11 and H-2/H-5/H-7, and between H-5 and H-7, indicated that H-2, H 3 -11, H-5, and H-7 were at a relatively close distance in space, or oriented in the same direction.…”
Section: Resultsmentioning
confidence: 99%
“…72 Stemona-lactams R ( 137 ) with a hydroxy group at C10 was obtained from the roots of Stemona tuberosa (Figure 5). 26 Yuea et al 27 found 9 a - epi -tuberospironine ( 138 ) from the roots of Stemona tuberosa (Figure 5). Hu et al 73 achieved 3 novel croomine group alkaloids, stemtuberlines C-E ( 139 - 141 ), from the roots of Stemona tuberosa (Figure 5).…”
Section: Phytochemistrymentioning
confidence: 99%
“…Schinnerl et al 23 obtained tuberostemonine N (26) from a mixture of Stemona species (Figure 3). In 2008, Lin et al 24 discovered tridehydrotuberostemonine, 9α-bisdehydrotuberostemonine (27), and 9α-bisdehydrotuberostemonine A (28), from the roots of Stemona tuberosa collected from Yunnan Province (Figure 3). 9α-Bisdehydrotuberostemonine A was the first sample of tuberostemonine-type alkaloid with an opened ring E, while 9α-bisdehydrotuberostemonine possesses a pyrrole ring.…”
Section: In 2002mentioning
confidence: 99%
See 1 more Smart Citation
“…sessilifolia and S . tuberosa , respectively. In our ongoing search for AChE‐inhibiting natural compounds, five new Stemona alkaloids ( 1–5 ) of the miscellaneous group according to Pilli's classification, or tuberostemonine group according to Greger's classification, were isolated from the EtOH extract of the roots of S. tuberosa .…”
Section: Introductionmentioning
confidence: 97%